1997
DOI: 10.1177/000348949710600906
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations on Acute Low-Tone Sensorineural Hearing Loss

Abstract: We retrospectively analyzed the clinical records of 137 patients who were treated at our clinic for acute low-tone sensorineural hearing loss of unknown cause over a period of 8 years. The analyses of the clinical records indicated the following clinical characteristics: female preponderance; peak incidence during the fourth decade of life; frequent accompanying tinnitus, sensation of ear fullness, and/ or autophony; suspicion of bilateral involvement; and association with autonomic imbalance. The hearing in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 11 publications
2
47
3
3
Order By: Relevance
“…This resulted in about one quarter of our cases being probable cases. Previously, the peak age of ALHL onset was reported to be in the late 40s to 50s [1,2,4,7]. In our study, the mean age at onset was 47.3 years; however, the mean age of patients with definite ALHL was 40.1 years and that of patients with probable ALHL was 66.6 years.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This resulted in about one quarter of our cases being probable cases. Previously, the peak age of ALHL onset was reported to be in the late 40s to 50s [1,2,4,7]. In our study, the mean age at onset was 47.3 years; however, the mean age of patients with definite ALHL was 40.1 years and that of patients with probable ALHL was 66.6 years.…”
Section: Discussioncontrasting
confidence: 59%
“…On the other hand, immunological studies [8,9] have suggested that autoimmunity is involved in the development of ALHL, so immunosuppressive drugs such as steroids are often given for ALHL via the oral [1,10], intravenous [1], or intratympanic [12] route. Adenosine triphosphate and vitamin B 12 are also used to improve circulation and metabolism in the inner ear [4]. The effectiveness of steroids, diuretics, adenosine triphosphate, and vitamin B 12 differs among reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical features of ALHL were afterwards detailed in several reports [2][3][4], and the fact that ALHL is an independent disease entity different from idiopathic sudden deafness has been established. First, Abe [1] reported that hearing loss was restricted to the low-frequency range, was very mild and might recover after a relatively short period, even without treatment.…”
Section: Introductionmentioning
confidence: 99%
“…First, Abe [1] reported that hearing loss was restricted to the low-frequency range, was very mild and might recover after a relatively short period, even without treatment. Recently, it was reported that in some ALHL patients the level of hearing loss fluctuates and/or progresses to Mé-nière's disease [2][3][4]. Concerning the etiology, Yamasoba et al [3] reported that the glycerol test was positive and -SP/AP ratios were abnormally increased in electrocochleography in most patients with ALHL, and concluded that ALHL might be caused by endolymphatic hydrops.…”
Section: Introductionmentioning
confidence: 99%